Metode Self Instructional Training untuk Menurunkan Kadar Gula Darah Pasien DM Tipe 2 - Nian Afrian Nuari (Journal of Ners and Midwifery, 2017)
Blood glucose levels  uncontrolled is a problem that is often found in patients with Diabetes Mellitus. This has an impact on the health of the patient as it would appear some macrovascular and microvascular complications. Number of patients with DM in Indonesia has increased every year and only 50% of patients suffering from diabetes who are aware of, and around 30% of them take medication regularly. The purpose of this study to determine the effect of Self Instructional Training method on blood glucose levels of patients. The method used is pre experiment with purposive sampling technique and the sample size of 16 respondents. Measuring instrument used glucometers to measure blood glucose levels and analyzed with Paired T Test. Based on the results, the entire blood glucose levels before the intervention above 200 mg /dl. After Self Instructional Training Intervention average blood glucose level was 35.75 mg /dl. Blood glucose levels are highest when the post test was 253 mg /dl and the lowest is 197 mg /dl. Based on Paired T Test  analysis obtained Self Instructional Training interventions can reduce blood glucose levels of patients with Diabetes Mellitus Type II (p value = 0.000). Diabetes Mellitus patients expected to be able to apply the  SIT method to perform self-care so that the patient's blood glucose levels can be controlled. Patient can do this methods  at home and needed support from their  family and health professionals to treat the diseases.